Electroactive composite scaffold with locally expressed osteoinductive factor for synergistic bone repair upon electrical stimulation. (February 2020) - Cui, Liguo; Zhang, Jin; Zou, Jun; Yang, Xianrui; Guo, Hui; Tian, Huayu; Zhang, Peibiao; Wang, Yu; Zhang, Ning; Zhuang, Xiuli; Li, Zhongming; Ding, Jianxun; et al.
Abstract: Tissue engineering is a promising strategy for the repair of large-scale bone defects, in which scaffolds and growth factors are two critical issues influencing the efficacy of bone regeneration. Unfortunately, the broad application of growth factors is limited by their poor stability in the scaffolds. In the present study, the strictly controlled expression of human bone morphogenetic protein-4 (hBMP-4) in the presence of doxycycline is achieved by adding an hBMP-4 gene fragment into a non-viral artificial restructuring plasmid vector (pSTAR) to form the pSTAR-hBMP-4 plasmid (phBMP-4). Furthermore, the controlled release of phBMP-4 is obtained with an electroactive tissue engineering scaffold, generated by combining a triblock copolymer of poly(l -lactic acid)- block -aniline pentamer- block -poly(l -lactic acid) (PLA-AP) with poly(lactic- co -glycolic acid)/hydroxyapatite (PLGA/HA). This PLGA/HA/PLA-AP/phBMP-4 composite scaffold, with controlled gene release and Dox-regulated gene expression upon electrical stimulation, operating synergistically, exhibits an improved cell proliferation ability, enhanced osteogenesis differentiation in vitro, and effective bone healing in vivo in a rabbit radial defect model. Taking these results together, the proposed smart PLGA/HA/PLA-AP/phBMP-4 scaffold lays a solid theoretical and experimental basis for future applications of such multi-functional materials in bone tissue engineering to help patients in need. Graphical abstract: Image 1